Law Applicable to Foreign Service Contracts - Sibel Özel (Public and Private International Law Bulletin)
Law Applicable to individual employment contracts are regulated separately in Article 27 of Turkish Private International and Procedural Law No. 5718 (MÖHUK) in terms of protection for weaker parties. In this respect, the parties are not allowed to choose a law that would deprive an employee of the protection afforded to them by the provisions of the law of the country in which the employee habitually carries out their work. The peremptory norms whose purpose is to protect employees regarding the law of the workplace will indicate employees’ level of protection. In this respect, MÖHUK differs from the Rome I Regulation on laws applicable to contractual obligations. MÖHUK does not allow a choice to be made regarding law that may result in an employee being deprived of the protection afforded to them by provisions that cannot deviate from an agreement under the law of the habitual place of employment. However, while the Rome I Regulation also doesn’t allow the law to be chosen that may result in an employee being deprived of the protection afforded to them by provisions that cannot deviate from an agreement under the law of the habitual place of employment, it also doesn’t allow this for the law in the country where the place of business through which the employee was engaged is situated, with the law of that country being more closely affiliated than indicated in Paras. 2 and 3 of Art. 8. In places where the parties did not choose a law, the applicable law must be determined by the objective criteria of the law of the habitual place of employment. However, when the employment contract is more closely affiliated with the law of another country, the law of that other country can be applied. Foreign service contracts that are concluded between Turkish employees taken abroad to work and their Turkish employers are prepared by the Turkish Employment Agency with regard to terms and conditions. These contracts include provisions related to the application of the law of the country where the employee works regarding certain issues. This article reviews if these provisions are the choice of a law agreement and a reason for applying Turkish law in addition to overriding mandatory rules in employment law and the effects of public policy.